Analisis Komparatif Kurikulum Merdeka dan Kurikulum Pendidikan Berbasis Karakter di Sekolah Dasar - Dendodi Dendodi; Nur April Yani Maharani; Ummutiara Antya Mujahiddita; Nabila Septrianti (Journal on Education, 2024)
In Indonesia, curriculum reforms have been carried out to adapt to the needs of the times, one of which is the Merdeka Curriculum which was introduced in 2022, replacing the 2013 Curriculum. The Merdeka Curriculum emphasizes learning flexibility, student-centeredness, and adaptation to individual interests and talents. On the other hand, the Character-Based Education Curriculum focuses on building character and moral values, with the aim of producing individuals with high integrity. This research compares the two curricula, provides a conceptual overview, and assists schools in selecting and adapting curricula that suit educational goals using a descriptive qualitative approach through research instruments in the form of interviews. It is hoped that the research results can make a significant contribution to curriculum development in Indonesia and become a reference for stakeholders in improving the quality of basic education.